2008
DOI: 10.4103/0019-5413.43393
|View full text |Cite
|
Sign up to set email alerts
|

Taylor spatial frame in the treatment of open tibial shaft fractures

Abstract: Background:The Taylor spatial frame (TSF) is a modern multiplanar external fixator that combines the ease of application and computer accuracy in the reduction of fractures. A retrospective review of our prospective TSF database for the use of this device for treating open tibial fractures in pediatric, adolescent, and adult patients was carried out to determine the effectiveness and complications of TSF in the treatment of these fractures.Materials and Methods:Nineteen male patients with open tibial fractures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 36 publications
2
21
1
Order By: Relevance
“…There is no significant difference between these two treatment methods in fracture healing time, deep tissue infection, and osteomyelitis in open tibial and femoral fractures [ 13 ]. Traditional circular fixators need excellent preoperative planning and careful application [ 5 ]. Computer-assisted external fixation systems are based on Ilizarov principles and provide similar stability to that of Ilizarov-type external fixators with easier application.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no significant difference between these two treatment methods in fracture healing time, deep tissue infection, and osteomyelitis in open tibial and femoral fractures [ 13 ]. Traditional circular fixators need excellent preoperative planning and careful application [ 5 ]. Computer-assisted external fixation systems are based on Ilizarov principles and provide similar stability to that of Ilizarov-type external fixators with easier application.…”
Section: Discussionmentioning
confidence: 99%
“…Computer-assisted external fixation systems are based on Ilizarov principles and provide similar stability to that of Ilizarov-type external fixators with easier application. Nowadays, they are more commonly used in the treatment of open fractures [ 5 , 14 , 15 ]. This study presents the use of the Spider Frame in open fractures, and to our knowledge, is the first paper in the literature about this computer-assisted system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Redness or tenderness near a pin (stage 1) or serous discharge (stage 2) or seropurulent or purulent discharge (stage 3) was taken as evidence of infection. The above classification set aside grades 4 and 5 of the Dahl classification [ 20 ] (4 = osteolysis requiring pin removal and 5 = ring sequestrum requiring debridement) which we presume are representative of a complicated infection. Swabs were taken from any pin-site with serous, seropurulent and purulent discharge for microscopy, culture and sensitivity.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies in recent years have reported on the successful use of hexapod‐based external fixators in clinical practice for various indications. In some of these studies, the authors define the achieved clinical accuracy as the amount of remaining bone deformity (angulation and torsion in degrees, and translation in millimeters or percentage of dislocation) . In other studies, the standard joint angle system established by Paley and colleagues is used as the reference to report clinical accuracy .…”
Section: Introductionmentioning
confidence: 99%